Financial prudence through financial education: A conceptual framework for financial inclusion - Arsyianti, Laily Dwi; Kassim, Salina (King Abdulaziz University Scientific Publishing Center, 2018)
This paper aims to develop a framework to improve financial prudence through financial education and financial inclusion for low-income households in Indonesia. Knowledge shapes attitude, which later influences behavior. A household, in terms of its social production function, needs to feel secure financially in order not to fall into insolvency or bankruptcy. Households that are equipped with better financial education and knowledge are more likely to undertake recommended financial behaviors. By targeting the low-income group through a financial inclusion agenda, the government, Islamic social finance practitioners, and academicians enable low-income households to act with financial prudence.